Early detection of osteoporosis in a general practitioner’s office - Kostić, Milena; Radosavljević, Olga; Vučković, Maja (General Practice, 2025)
Introduction. Certain risk factors play a significant role in the development of osteoporosis, the early recognition of which can affect the appearance, course and outcome of the disease.Objective. To examine the possibilities and importance of early detection of patients at increased risk for developing osteoporosis in a GP's office.Method. The research was conducted in an outpatient clinic of the Health Center in Lazarevac, in the period September-December 2016. Data on risk factors for osteoporosis, obtained during a visit to a GP and using medical records, were collected. Subjects with one or more risk factors were referred for bone mineral density (BMD) measurement using DEXA, and according to the BMD and risk factors findings to a rheumatologist. Data were analyzed using descriptive statistics and statistical hypothesis testing methods, analyzed using SPSS 20.Results. 58 postmenopausal women over 45 years old, average age 65.62 years, participated in the research. The most prevalent risk factors were: early menopause (32.8%), cigarette smoking (31.0%) and the presence of a chronic disease (25.9%). 51.7% had 1 or 2 risk factors, 22.4% 3 or more risk factors. 72.4% of the subjects were referred for DEXA, 35.7% were diagnosed with osteoporosis and treatment was started.Conclusion. In a general practitioner's office, people at increased risk for osteoporosis can be detected in a simple way, by examining the risk factors for its occurrence. Further health intervention ensures prevention, timely diagnosis and treatment of this disease.
Keywords: Key words: postmenopausal osteoporosis, risk factors, early diagnosis